Design and Implementation of Digital Teaching Platform for Xinjiang Folk Song Sight Singing Based on Mobile Phone - Guojun Sun, Xiaowei Zhang (Forest Chemicals Review)
With the development of science and technology and the progress of society, the achievable functions of mobile phones have penetrated into all fields of people’s lives, including music education and teaching. Music sight singing teaching on mobile terminals, such as the development and design of online learning programs for Xinjiang folk song sight singing teaching, has become possible. The author takes the design and implementation of the digital teaching platform for Xinjiang folk song sight singing as an example, expounds from the design and operation to the final implementation, aiming to provide theoretical reference and practical basis for related research.